A Study on the Creative Approach of Luo Zhenyu’s Oracle Bone Calligraphy - wu, zongyang (Pacific International Journal, 2023)
In the history of Chinese culture, the oracle bone script, along with the Dunhuang documents, the Han jian of the Western region, and the Great Treasury of the Cabinet, are known as the four major discoveries of the twentieth century. The oracle bone script has a history of more than 3,000 years. In the field of philology and archaeology, its appearance has brought original materials for the examination of the origin of Chinese characters; in the field of art, its appearance is a great asset for the study of oracle bone script calligraphy. From the dimension of the study of the history of calligraphy, the oracle bone script already possesses the three basic elements of calligraphy: the brush, the knotted character, and the chapter, and is the earliest system of writing with a more mature system and aesthetic nature in the development of Chinese writing. From the perspective of the pen, the oracle bone script was carved with a knife on hard turtle shells or animal bones, so the lines of the script are mainly straight lines of uniform thickness, showing a slightly thicker middle and slightly thinner ends, showing the aesthetic characteristics of thinness and solidity, uprightness and sharpness, giving people a strong three-dimensional sense and visual impact. As a script, oracle bones have both their linguistic communication and their calligraphic artistry.We examine oracle bone calligraphy in terms of writing instruments, brushwork, and chapter forms. The purpose of this paper is to identify problems and analyze them in a step-by-step manner by using a logical tree model of deduction through writing practice and documentary evidence to explore the feasibility of oracle bone calligraphy from three aspects: writing materials, brush structure, and composition form